Salivary Lactate Dehydrogenase (LDH) as a Marker for Radiation-induced Mucositis in Head and Neck Cancers: A Preliminary Study - Arnadi Shivashankara (Middle East Journal of Cancer, 2019)
Background: In this study, we sought to understand the usefulness of salivary lactate dehydrogenase as a predictive marker for the development of radiation-induced mucositis. Methods: This was a prospective study with head and neck cancer patients who required curative radiotherapy (>60Gy). We collected patients’ saliva before the onset of radiation and after 2 Gy of radiation to assess lactate dehydrogenase levels. The patients received the stipulated oral and dental care. Data on incidence and severity of mucositis was collected using a preform sheet and oral mucositis assessment scale published by the Radiation Therapy Oncology Group throughout the 7-week treatment period. Results: Salivary lactate dehydrogenase increased with exposure to radiation (P<0.0001) and there was an observed association with mucositis severity (P<0.0001; r = 0.515). Conclusion: The present results have established, for the first time, that salivary lactate dehydrogenase could be a useful predictive marker to understand the development of radiation-induced mucositis in patients with head and neck cancer. The proximity of the oral cavity for regular observation and saliva collection is an added advantage.